2020
DOI: 10.1016/j.heliyon.2020.e04431
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of thymol against adrenaline-induced myocardial injury in rats

Abstract: Cardiovascular disease represents a vital global disease burden. This study aims to assess the possible cardioprotective effect of thymol against adrenaline-induced myocardial injury (MI) in rats. Furthermore the effect of thymol on cardiac function biomarkers, electrocardiogram (ECG) alterations, oxidative stress, inflammation, apoptosis and histopathological changes was assessed. MI was induced by adrenaline (2 mg/kg, s.c.) injected as a single dose for 2 consecutive days (24 h apart). Normal and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Even though L. gracilis, H. spicigera and E. stipitate aren't studied through the healing optics, there is evidence in the literature, that the compounds present in those species, such Thymol, α-Pinene, and Guaiou also induces a healing activity (Najafloo et al, 2020;García-Salinas et al, 2020;Pivetta et al, 2018). Moreover, it has antimicrobial activity (Kazemi-Pasarvi et al, 2020), antioxidant (Gursul et al, 2019), anticarcinogenesis (Li et al, 2017), and cardioprotective (El-Marasy et al, 2020). α-Pinene is effective against inflammation by suppressing activation of the MAPK/NF-B pathway, which consists in the inhibition of mitogen-activated protein kinases (MAPKs), and preventing extracellular signal-regulated protein kinase phosphorylation (ERK), as well, c-Jun NH2-terminal kinase (JNK).…”
Section: Resultsmentioning
confidence: 99%
“…Even though L. gracilis, H. spicigera and E. stipitate aren't studied through the healing optics, there is evidence in the literature, that the compounds present in those species, such Thymol, α-Pinene, and Guaiou also induces a healing activity (Najafloo et al, 2020;García-Salinas et al, 2020;Pivetta et al, 2018). Moreover, it has antimicrobial activity (Kazemi-Pasarvi et al, 2020), antioxidant (Gursul et al, 2019), anticarcinogenesis (Li et al, 2017), and cardioprotective (El-Marasy et al, 2020). α-Pinene is effective against inflammation by suppressing activation of the MAPK/NF-B pathway, which consists in the inhibition of mitogen-activated protein kinases (MAPKs), and preventing extracellular signal-regulated protein kinase phosphorylation (ERK), as well, c-Jun NH2-terminal kinase (JNK).…”
Section: Resultsmentioning
confidence: 99%
“…The myocytes loss seen in the DEX group may be due to apoptosis or necrosis and hyperplasia of the myocytes (Mandarim‐de‐Lacerda & Pereira, 2000). A study has reported that prolonged MI is followed accompanied by cell death and ultimately myocardial fibrosis resulting in a decrease in cardiac function which is reversed by phenolic compounds and antioxidants (El‐Marasey et al, 2020). Cell death usually results in a decrease in cardiac nuclei count and our study collaborates with a previous study that reported low cardiac nuclei to count due to myocardial injury (Korashy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It also has anti-inflammatory (through decreasing cytokines and chemokines recruitment) and antioxidant properties (through scavenging of free radicals, augmenting the non-enzymatic and enzymatic antioxidants, and chelation of metal ions) ( Nagoor Meeran et al, 2017 ), antimicrobial (through disruption of the bacterial plasma membrane's lipid portion, resulting in intracellular material leakage) ( Trombetta et al, 2005 ), anticarcinogenic (via apoptosis induction, anti-proliferation, angiogenesis and migration inhibition by modulation of carcinogen metabolising enzyme activity) ( Salehi et al, 2018 ), antispasmodic (via opposing Ca 2+ activation and the ATP-dependent activity of the muscle) ( Tamura and Iwamoto 2004 ), growth enhancer (via increasing antioxidant and digestive enzyme activity, as well as an improved immunological response, which may have a positive impact on health and performance) ( Hashemipour et al, 2013 ), and immunomodulatory (via increasing the expression CD4, CD8, and Th1 cytokines through increased IFN- γ expression and increased interleukin-12 release ( Chauhan et al, 2010 ). Furthermore, it exhibits hepatoprotective ( Jafari et al, 2018 ), nephroprotective ( Jamshidi and Taheri 2021 ), and cardioprotective properties ( El-Marasy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%